PENDAMPINGAN PENDIRIAN UKM ELANG JAWA MELALUI MESIN PEWARNAAN BATIK DAN HKI - Susantiningrum Susantiningrum; Kristiandi Kristiandi; Subroto Rapih (Jurnal Kewirausahaan dan Bisnis, 2019)
UKM Elang Jawa and UKM Ontorejo is an SMEs engaged in batik craft in Sragen Regency. In the batik production process, these SMEs have difficulties in the process of coloring batik, more on color alignment for the purposes of coloring cloth with a length of fabric that exceeds 2.5 meters in length and is less effective in the use of coloring agents. Another problem is the lack of business legality in both SMEs. The purpose of this activity is to improve the technology that can support the development of traditional batik businesses UKM Elang Jawa and UKM Ontorejo through appropriate technology using Batik Coloring Machine (Feeder), business assistance and business legality management assistance with technical assistance, management training and entrepreneurship, and mentoring intensively and sustainably. Activities that have been carried out include the initial activities, the supply of feeder machines, and training in the use of feeder machines.Keywords: batik, feeder, legality, business, technology